Moda y autoconcepto: la construccion de la identidad a traves del estilo. (2024)
This monograph examines the definition, evolution of fashion and its impact on psychological variables such as self-concept and self-esteem. Clothing, which began as a survival necessity, was transformed into a symbol of social status with the nobility and was later democratized with the massification of textiles. However, current consumerism has created a gap, where staying ahead is again exclusive to the upper classes. In addition, social networks have intensified the visibility of fashion, driving "fast fashion" and creating an aesthetic pressure that can negatively affect self-esteem, especially among young people when they feel the need to replicate these trends and styles without exception. Despite this pressure, fashion can be a tool for personal expression, reinforcing confidence and emotional well-being when adapted to individual style. Likewise, its therapeutic potential in emotional recovery is highlighted, being useful to improve the self-image of those who have suffered trauma or wish to reaffirm their identity.